Literature: an Important Hermeneutical Mediation for Theology - Avenatti de Palumbo, Cecilia Inés (Concilium, 2017)
The article proposes a renewal of theology's approach through a consideration of the role of creative imagination characteristic of literature as an aesthetic activity. Through an evaluation of the interdisciplinary status of the dialogue between theology and literature, it lists the successes and the limits of the process that has taken place since the Second Vatican Council until now. The ineffectiveness of the paths taken to produce a real transformation of theological language has led the author to explore other possibilities. The change consists in theology's looking at itself in the mirror of the creative imagination, the core of literary activity, in order to produce a renewal in the process and approach of theological thinking. In short, the aim is to bring back imagination and action to revitalise theology by taking it back to the creative power that was its original source.